2017
DOI: 10.1042/bsr20170149
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-98 interferes with thrombospondin 1 expression in peripheral B cells of patients with asthma

Abstract: Thrombospondin 1 (TSP1)-producing B cells are an important immune regulatory cell fraction in the body, which are compromised in a number of immune diseases. miRs are involved in the immune regulation. The present study aims to elucidate the mechanism by which miR-98 interferes with the expression of TSP1 in B cells of the peripheral blood system. In the present study, peripheral blood samples were collected from patients with allergic asthma. The B cells were isolated from the blood samples to be analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…All of these miRNAs have been shown to play roles in asthmatic inflammation. It was demonstrated that increased miR-98 in peripheral blood may contribute to pathogenesis of asthma by lowering the frequency of immune regulatory B cells [12] . There is some evidence to suggest that Let-7 has a pro-inflammatory role in asthma, primarily by promoting type 2 inflammation [13,14] .…”
Section: Association Of Mirna Expression Patterns With Mild Non-eosimentioning
confidence: 99%
“…All of these miRNAs have been shown to play roles in asthmatic inflammation. It was demonstrated that increased miR-98 in peripheral blood may contribute to pathogenesis of asthma by lowering the frequency of immune regulatory B cells [12] . There is some evidence to suggest that Let-7 has a pro-inflammatory role in asthma, primarily by promoting type 2 inflammation [13,14] .…”
Section: Association Of Mirna Expression Patterns With Mild Non-eosimentioning
confidence: 99%
“…MiRNAs have been linked to TGFβ-signaling pathway in a variety of diseases, usually in studies which only examined few miRNAs and genes within the signaling pathway. For instance, miR-181a has been shown to have its expression altered by TGFβ [ 24 , 25 ], miR-494 and miR-126-5p have been linked to BMP4 in the regulation of angiogenesis [ 26 ]; miR-98 with TBSP1 expression in asthma [ 27 ]; miR-590-5p with downregulation of TGFβ signaling in cardiosphere-derived stem cells [ 28 ]; the miR-17-92 cluster with cell proliferation in mouse mesenchymal cells [ 29 ]; and miR-140-5p with tumor growth [ 30 ]. MiRNAs have also been linked with various disease processes in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…miR-147 also reduces the production of inflammatory proteins induced by TLR2, TLR3, and TLR4-mediation [27]. miRNA-98 has been implicated to be involved in asthma by modulating peripheral B cells which is an important immune regulatory cell, via interfering the expression of thrombospondin 1 [28]. miR-10a mediates airway hyperresponsiveness by suppresses cell proliferation of airway smooth muscle, via targeting BDNF in asthmatic rats [29].…”
Section: Discussionmentioning
confidence: 99%